Estudos e modelagem do comportamento hidrodinâmico de lagoas de polimento - Ricardo Gomes Passos (2017)
The efficiency of stabilization ponds is closely related to hydrodynamic factors that may occur within these systems. Inference about some of these factors (eg, short circuit, dispersion degree and stagnation zones) is possible through the stimulus-response technique with tracers. However, influence of phenomena such as thermal stratification, vertical mixing, wind effects, turbulence, presence of sludge and recirculating flows can best be described with analysis of other field data, such as measurements along the vertical profile of the pond, use of hydraulic measurement devices, dye, weather data, and/or use of more advancedcomputational flow analysis tools; being the Computational Fluid Dynamics (CFD) an excellent example, with increasing application in the area. In order to evaluate the hydrodynamic behavior of ponds and their relationship with design caracteristics, operation and external environmental factors, the aforementioned tools were used for studies and modeling in two polishing ponds in different operational configurations, designed to small communities. Results of the vertical profile monitoring demonstrated daily thermal stratification events followed by destratification and vertical mixing, in both ponds andoperation phases, as well as great influence of the sludge on the thermal balance. Tracer tests and flow analysys tests revealed typical velocities, trajectories and trends of hydrodynamic behavior in ponds - such as high degree of short-circuiting and general tendency of complete mixing - as well as practical records regarding the use of these techniques, as warnings about the use of table salt as a tracer and restrictions on the use of hydraulic devices and flow meters. CFD models were developed considering the contour conditions and interactions with environment most relevant to ponds, and contributed to reinforce the importance of the tool in the hydrodynamic analysis of these systems. The models (calibrated and validated) were used in conjunction with field data and allowed a detailed hydrodynamic analysis, thus allowing evaluations and diagnoses of existing units, project improvements, operational interventions to improve efficiency and possible suggestions for advances in studies and modeling of these systems.